The safety and effectiveness of salvianolate in preventing perioperative venous thromboembolism in China: A PRISMA-compliant meta-analysis based on RCTs. Issue 18 (7th May 2021) - Chai, Yu-na; Luo, Mi; Liang, Wei-jie; Qiu, Jian-li; Li, Dangchi; Wang, Li-chong; Tu, Xing; Liu, Cheng-ye; Qin, Chong-Zhen; Li, Duo-lu
Abstract: Background: Salvianolate, a common drug for stabilizing heart disease and Angina Pectoris, is considered to be off-label for preventing venous thromboembolism (VTE) or anticoagulation at present. However, many clinical studies have showed that salvianolate can effectively inhibit the deep-vein thrombosis (DVT) incidence, and prevent VTE of perioperative patients in the real world in China. Objective: This analysis aimed to evaluate the effectiveness and safety of salvianolate in preventing VTE in perioperative patients. Methods: Databases of PubMed, Cochrane Library, Embase, CNKI, Wanfang and VIP were searched until July 2019. Literature retrieval, data extraction and quality assessment were independently completed by two researchers and checked with each other. Review Manager 5.2 software was applied for meta-analysis. Results: A total of 429 studies were retrieved, including 11 randomized controlled trials (RCTs) with a total of 1149 subjects. Compared with low molecular weight heparin (LMWH) group alone, salvianolate combined LMWH group had lower DVT incidence in preventing perioperative thrombosis (2.75% and 14.23%, OR: 0.21, 95% CI:[0.08, 0.53]; P = .0009). The incidence of adverse reactions of experimental group was similar to that of control group (1.79% and 2.31%, OR: 0.65, 95% CI:[0.18, 2.35]. P = .51). Compared with the control group, D-dimer level (D-D), platelet count (PLT), fibrinogen (FIB), whole blood high shear viscosity (WBHSV), and whole blood low shear viscosity (WBLSV) were all significantly decreased ( P < .01), and prothrombin time (PT) was significantly increased ( P < .05). Conclusion: Salvianolate combined LMWH has better effectiveness and the same safety in preventing venous thromboembolism in perioperative patients. However, due to the small number of included literatures, large sample studies are still needed to further verify this conclusion. Abstract : Supplemental Digital Content is available in the text